Catalytic removal of nitrates from waters in a continuous flow process: The remarkable effect of liquid flow rate and gas feed composition - Costa, Costas; Savva, Petros G.; Theologidis, Christodoulos (My University, 2011)
The selective catalytic reduction of nitrates (NO3 -) in water mediums towards N2 formation by the use of H2 and in the presence of O2 (air) in the gas feed has been investigated under a continuous flow process over Pd-Cu supported on various mixed metal oxides, xwt.% MxOy/g-Al2O3 (MxOy=CeO2, MgO, Mn2O3, Cr2O3, Y2O3, MoO2, Fe2O3 and TiO2). It is demonstrated for the first time that a remarkable improvement of both catalysts activity and N2 reaction selectivity can be achieved when increasing the liquid flow rate in the continuous flow process. In particular, it was found that NO3 - reduction rates up to more than two times higher and NH4 selectivity values up to twenty times lower can be obtained when increasing the liquid flow rate from 2 to 6mL/min. Moreover, it was proven for the first time, in a continuous flow process, that the presence of oxygen (or air) has a remarkable positive effect on the reaction's selectivity towards nitrogen. The reaction's selectivity towards NH4 can be decreased by up to three times when 20vol.% air is added in the gas feed of the NO3 -/H2 continuous flow reaction. The Pd-Cu clusters supported on TiO2-, CeO2- and MgO-coated g-Al2O3 spheres showed the best catalytic behaviour compared with the rest of supports examined, both in the presence and in the absence of oxygen in the reducing feed gas stream. In addition, it was found that the initial concentration of nitrates in the liquid feed can significantly affect catalysts activity and reaction's selectivity. A positive apparent reaction order towards nitrates of 0.9 was calculated on Pd-Cu/TiO2/Al2O3. 2010 Elsevier B.V.
Keywords: Catalytic denitrification; CSTR; Nitrates reduction; Nitrates removal; Supported Pd-Cu